Gastroprotective Activity of Fruit Ethanolic Extract of Tetrapleura tetraptera on Indomethacin-Induced Ulcer in Rats - Oloyede, H.O.B.; Olugbode, A.E.; Salawu, M.O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2018)
Tetrapleura tetraptera (Schum. & Thonn.) Taub. is an important fruit that has many ethno-medicinal uses suchas anti-ulcer and nutritive agent. The present study investigated the gastro-protective activity of ethanolicextract of Tetrapleura tetraptera fruit against indomethacin-induced ulcer in rats. For this study, thirty six rats(150-200 g) were separated into six groups of six rats each. For 14 days before ulcer induction withindomethacin, the animals received once daily oral doses of distilled water (groups 1 and 2), omeprazole 20mg/kg body weight (group 3), and ethanolic extract of T. tetraptera fruit at doses of 50, 100 or 200 mg/kg bodyweight (groups 4, 5 and 6 respectively). After the last treatment, all the animals except group 1 were fasted for18 hours with access to water only and treated with 100 mg/kg body weight of indomethacin to induce ulcer. Theanimals were sacrificed 6 hours after ulcer induction and the stomach was removed for biochemical andhistological analysis. T. tetraptera fruit extract significantly (p < 0.05) decreased gastric secretion volume, meanulcer index, total acidity, total protein and pepsin secretion relative to indomethacin-induced ulcerated rats. Theextract also significantly (p< 0.05) increased mucin content relative to the ulcerated untreated rats. These resultswere similar to those achieved by pretreatment with omeprazole. The activity of glutathione peroxidase andreduced glutathione concentration in the animals treated with 200 mg/kg body weight T. tetraptera fruit weresignificantly increased (P< 0.05) compared to the negative control. The fruit extract also significantly reduced(P< 0.05) the concentration of malondialdehyde and myeloperoxidase activity over the ulcerated untreated rats.Similarly, the histological analysis showed that T. tetraptera fruit extract prevented indomethacin-mediateddisruption of the mucosal wall of the stomach. This study shows that Tetrapleura tetraptera possesses gastroprotective properties which may be attributed to the presence of flavonoids, phenolics and tannins.